The Effect of Oxygen Therapy on Oxidative Stress Index in Patients with Acute Myocardial Infarction; a Letter to the Editor - Afshin Amini; Abbas Mahdavipour (Archives of Academic Emergency Medicine, 2018)
Tissue hypoxia is a key factor for cell death after acute myocardial infarction (MI). It seems that increase in the relative oxygen pressure in inhaled air can be an effective treatment option for treating acute MI. However, contradicting findings and results have been published regarding using oxygen therapy in patients with acute MI (1, 2). Some researchers have believed that generation of free radicals, induction of oxidative stress, and damage to cell membrane are among side effects of O2 consumption (3, 4). It has been shown that O2 therapy can increase microvascular resistance, result in a decrease in coronary blood flow and cardiac output, and bring about numerous negative effects such as increase in the risk of arrhythmia and cellular damage (4).